Intra- and inter-personal factors of psychosocial status in Slovenian military personnel with regard to their traumatic event experience - Selič, Polona (Zdravstveno varstvo, 2011)
Problem: The main objectives of this study were to identify differences in thepsychosocial status of military personnel who had and who had no traumatic event experience, and to screen for potential mental health vulnerability related to post-traumatic stress. Methods: 390 military personnel were included in the study, with 103 of them reporting traumatic event experience. The Mini-International Neuropsychiatric Interview Screening for Post-TraumaticStress Disorder, the CAGE instrument, the Eysenck Personality Scales, the Folkman-Lazarus Ways of Coping Questionnaire, the Rosenberg Self-Esteem scale and self-evaluative questions about important relationships were administered. Results: The respondents who reported traumatic event experience (TEE) also reported a significantly higher frequency of other stressful events, a significantly more frequent past history of depression (16.5 % of respondents with TEE and 6.2 % of respondents without TEE) and significantly higher risky alcohol drinking; the latter, however, is not higher than the estimate for the total Slovenian population (10.7 % of respondents with TEE and 2.7 % of participants without TEE). Respondents with TEE smoke less frequently than respondents who reported no TEE (46.6 % vs. 60.1 %), and more often rely on self in stressful situations. There was no significant difference between the respondents with reported TEE and those without TEE in their personality traits, coping styles, and self-esteem, or inthe majority of job- and family-related factors. No difference was found between male and female personnel as concerns intra-personal factors and in stress- related behaviour. Conclusions: Intra-personal factors (personality, coping styles, and self-esteem) of military personnel indicate good personal potential for resilience. Stress-related substance (ab)use, especially smokingrates well above the Slovenian average, need further attention. (Abstract truncated at 2000 characters)
Keywords: psihosocialni status; stres; Trauma; travma; vojaško osebje